A tailoring guide to pattern drafting - Lawton, Katerina (New York, NY : Routledge, 2023)
"A Tailoring Guide to Pattern Drafting offers pattern drafting instructions for men's most popular tailored garment styles from 1850 to 1900 used in theatres and film productions today. The book features a wide range of 19th century garments, providing information and detailed instructions on the frock coat, morning coat, lounge jacket, smoking jacket, shirt, waistcoats, trousers, and long-riding breeches. It includes a brief history of each garment, accompanied by colourful illustrations and easy-to-follow instruction to draft historical 19th-century silhouettes for modern performances. The book features: - A brief history of each garment, accompanied by full-colour illustrations. - Modern step-by-step instructions with clear diagrams to draft 19th-century menswear. - Instructions incorporating both the imperial and metric systems. - Recommendations on choosing the appropriate modern-day equivalent fabric. - Recommendations on the quantity of the fabric. - Recommendations on the button size to make the garment appear more authentic. - A table of Dress Code Ethics for Gentlemen from 1850 to 1900. - Descriptions and visual information on how to take accurate measurements. - Photographs of costumes and images of the 19th-century Carte de Visite for visual support. A Tailoring Guide to Pattern Drafting is intended for anyone with a desire to learn or refine their costume cutting skills for theatre and film production. The book is aimed at undergraduate and graduate students, tutors, and both amateur and professional makers interested in the subject. To access the author's YouTube channel, featuring 130 step-by-step lessons to make a 19th Century Morning Coat using classical tailoring techniques, visit www.routledge.com/9780367265335"--
Volume 1. 1850-1900 Menswear for theatre and film
Keywords: Tailoring -- Pattern design; PERFORMING ARTS / Theater / General